Africanity and research: A case study in rural South Africa - Christina Landman; Hannelie Yates (HTS Teologiese Studies/Theological Studies, 2017)
In the first part of this article, Africanity as a concept within research methodology is exploredin the dialogical spaces between the binaries of racial identity and group identity, indigenousand traditional values, post-colonialism and post-racialism, blackness and African, as well aseliminativist and conservationalist. In the second part, the research carried out in twotownships in the eMakhazeni Local Municipality in Mpumalanga, South Africa’s most easternprovince, is described in terms of parameters and process. The townships involved areSakhelwe in Dullstroom-Emnotweni and Emthonjeni in Machadodorp-eNktokozweni. Theresearch focuses on interviews with young people between the ages of 18 and 24 on thepotential of faith-based organisations to assist them in moving from the ’margins‘ of society topositions of social cohesion. The third and main part of the article, is dedicated to lessonslearnt and experience acquired when research is carried out in a rural area from an Africanityperspective. This entails, inter alia (1) to be sensitive towards power relations in research; (2)respecting indigenous values within group identities; (3) not predefining the youth, usingindigenous (and not European) definitions of ‘agency’ and ‘marginalisation’; (4) to engage inobservation rather than interpretation; and (5) to decolonise the research process whenregarding interpretation as an act of colonisation.